2018
DOI: 10.4081/oncol.2018.366
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and its receptor polymorphisms: New possible prognostic biomarkers in leukemias

Abstract: Several factors such as chromosomal translocations, gene mutations, and polymorphisms are involved in the pathogenesis of leukemia/lymphoma. Recently, the role of vitamin D (VD) and vitamin D receptor (VDR) polymorphisms in hematologic malignancies has been considered. In this review, we examine the possible role of VD levels, as well as VDR polymorphisms as prognostic biomarkers in leukemia/lymphoma. Relevant English language literature were searched and retrieved from Google Scholar search engine (1985-2017)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…In contrast, it was shown that allele A exhibited a significant association with the occurrence of the illness in both CLL and NHL, as indicated by the odds ratio. These results correspond with those of Pezeshki et al, who found that the CT genotype (Fok1) was significantly associated with CML, while the T allele could be considered a prognostic agent ( Pezeshki et al, 2018 ). However, it should be noted that the findings of this current study do not agree with previous investigations, which indicated that the CC genotype, Fok1, demonstrated lower prevalence in the chronic lymphocytic leukemia (CLL) group in comparison with a healthy control group ( Rajab et al, 2015 ).…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, it was shown that allele A exhibited a significant association with the occurrence of the illness in both CLL and NHL, as indicated by the odds ratio. These results correspond with those of Pezeshki et al, who found that the CT genotype (Fok1) was significantly associated with CML, while the T allele could be considered a prognostic agent ( Pezeshki et al, 2018 ). However, it should be noted that the findings of this current study do not agree with previous investigations, which indicated that the CC genotype, Fok1, demonstrated lower prevalence in the chronic lymphocytic leukemia (CLL) group in comparison with a healthy control group ( Rajab et al, 2015 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, the limitation of vitamin D-affect therapy is the need for high concentration of vitamin D to reach therapeutic effect, which might cause systemic side effects [ 134 , 135 , 136 ]. Several methods are possible to overcome the barriers we face currently, including possible oral supplementation [ 132 ], select patient according to receptor polymorphisms [ 137 ], gene therapy involving CYP27B1 treatment [ 126 ].…”
Section: Application Of Natural Products In Aml Therapymentioning
confidence: 99%
“…However, probably not all individuals have the same needs for vitamin D 3 , i.e., it is questionable, whether a threshold level of the vitamin D status is an optimal reference. Nevertheless, patients with hematological diseases often have a low vitamin D status, which is associated with an unfavorable prognosis [146][147][148][149].…”
Section: Impact Of Vitamin D Status and Response Indexmentioning
confidence: 99%